الاغتراب الثقافي ومواجهته في الفكر التربوي المعاصر - أبو شعيرة خالد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تلقي هذه الدراسة الضوء على الاغتراب الثقافي؛ كتحدٍ يواجه الهوية الثقافية في الفكر التربوي المعاصر، واقتضت طبيعة المنهج الوصفي التحليلي المتبع في هذه الدراسة استجلاء مفهوم الاغتراب لدى نماذج من المنظرين المعاصرين، والكشف عن مؤشراته ومظاهره السائدة والعوامل التي تسهم في شيوع هذه الظاهرة.وقد خلصت الدراسة إلى أنّ الاغتراب ظاهرة ثقافية تؤدي إلى انتقال المجتمع وتحوله من طور الثقافة التقليدية إلى طور الثقافة الدخيلة الوافدة، كما أنهُ يهدد النظم الاجتماعية والاقتصادية والثقافية، كما أنه يظهر بوضوح في المؤسسات التربوية؛ كالأسرة والمدرسة والجامعة وعند الطالب والمعلم، كما أنّ هناك مؤشرات تعطي دليلاً واضحاً على مدى الاغتراب؛ كالعزلة الاجتماعية، واغتراب اللامعنى، وفقدان المعايير، واغتراب الذات، وفقدان السيطرة وإذا ما تحقق أحد هذه المؤشرات حكم على الهوية الثقافية بالاغتراب. وخرجت الدراسة بتصور مقترح للهوية الثقافية العربية من خلال الفكر التربوي المعاصر يعمل على وحدة الثقافة وعدم تفككها وطمسها وتهميشها ولا سيما في ظل التحديات العالمية والقوى المؤثرة. يعمل على بناء شخصية عربية قادرة على التفاعل الإيجابي مع غيرها من الهويات مع المحافظة على خصوصيتها الثقافية من خلال تخليص الطلبة في المدارس والجامعات من ازدواجية المفاهيم وإحداث اندماج اجتماعي وسياسي للمجتمع العربي ، وأن يكون للإعلام دور في التركيز على القضايا الفكرية والسياسية والدينية والأخلاقية والثقافية ، والتأكيد على مبدأ الأصالة والمعاصرة ، الذي يقتضي الإفادة من كل المستجدات والاتجاهات النافعة والانفتاح على كافة التجارب العالمية . Thisstudy highlights the cultural alienation as a challenge facing the cultural identity in the contemporary educational thought. The nature of the analytic descriptive approach used here requires clarifying the alienation concept in the models of contemporary theoreticians, and finding out its indications, manifestations, and factors which influence it. The study concludes that the phenomenon of cultural alienation leads to transforming the society from traditional culture into an intermediating one. It also threatens the social, economic, cultural and political systems. In addition, it is found clearly in educational institutions as family, school, and university as well as teacher and student. There are indications that give a clear evidence of the alienation such as social isolation, alienation of the meaninglessness, losing standards, self-alienation, and loss of control. Finally, has one of these indications been achieved, our cultural identity would have been judged as alienated. The study concludes, through contemporary educational thought,witha proposal for the Arabic cultural identity working on the unity of culture, not to break it or ignore it, especially in the light of global challenges, and leading to build a prominent Arab character which is able to interact positively with others from those identities, while maintaining the privacy of the Arabic culture, by helping students, in schools and universities to get rid from theconcepts’ duplication, creating social integration for Arab Community, a critical role for media in emphasizing the mental, political, and religious issues, andoriginality and contemporariness which requires the use of all recent development and useful attitudes, necessary for us to be open on world’s experiences and to take what fits our home and nation.